High-pressure homogenization and pH-shifting modification of hazelnut protein isolates: Functional enhancement, allergenicity reduction, and probiotic microencapsulation performance - Atalar, Ilyas; Elen, Hatice; Gul, Osman; Kurt, Abdullah; Aksu, M. Irfan; Konar, Nevzat (WILEY, 2026)
BACKGROUND Plant-based proteins, such as hazelnut protein isolates (HPIs), often exhibit limited solubility and functionality, as well as allergenic potential, thereby limiting their applicability in food products. This investigation sought to improve the techno-functional characteristics of HPI and mitigate its allergenicity via high-pressure homogenization treatment (HPHT) coupled with pH shifting, and to assess the feasibility of the modified HPI as a wall material for probiotic encapsulation.RESULTS The combined application of alkaline pH (pH 12) and high pressure (875 bar) substantially enhanced protein solubility (up to 86.5%) and emulsion activity; concurrently, the zeta potential became more negative, suggesting increased electrostatic repulsion. Structural investigations demonstrated significant conformational alterations, including the disruption of alpha-helix and beta-sheet structures and an increase in random coils, which, in turn, exposed hydrophobic groups and augmented surface hydrophobicity. These structural changes, crucially, modified protein epitopes, leading to a 49% decrease in HPI allergenicity. Furthermore, when assessed as a wall material for spray-drying microencapsulation of Lactobacillus acidophilus, the modified HPI, in conjunction with maltodextrin (1:1 ratio), displayed the greatest protective capacity, preserving 7.96 log CFU mL-1 viability post-drying and 7.22 log CFU mL-1 survival under simulated gastrointestinal conditions.CONCLUSION The findings demonstrate that altering the structure of the HPI via HPHT and pH modulation enhances its solubility and emulsifying characteristics while simultaneously reducing its allergenic potential, thus supporting its use as a viable wall material. As a result, this approach offers a potentially beneficial method for converting hazelnut meal by-products into adaptable, hypoallergenic ingredients for functional food applications.
Keywords: high-pressure homogenization treatment; hazelnut protein isolate; pH modification; allergenicity; probiotic encapsulation; RHEOLOGICAL PROPERTIES; MILK; Agriculture; Chemistry; Food Science & Technology